2020
DOI: 10.1055/s-0039-1698784
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy Rate in Thyroid Nodules with Atypia or Follicular Lesion of Undetermined Significance

Abstract: Introduction Atypia of undetermined significance (AUS) or follicular lesion of undetermined significance (FLUS) is one of the six diagnostic categories of the Bethesda System for Reporting Thyroid Cytopathology. The prevalence of malignancy among Bethesda category III cytology is variable, ranging from 5% to 37% in the literature. Objective To determine the rate of malignancy in thyroid nodules reported as Bethesda category III. Methods A total of 495 patients underwent surgical interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In our study there were no NIFTP cases diagnosed after the NIFTP entity was introduced in 2016 or in former cases which evaluated respectively. If AUS/FLUS cases underwent surgery the most common malignancy was PTC followed by FC in histopathological examination (15,16). Similarly, in our study 90.9% (10/11) of tumors were PTC.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our study there were no NIFTP cases diagnosed after the NIFTP entity was introduced in 2016 or in former cases which evaluated respectively. If AUS/FLUS cases underwent surgery the most common malignancy was PTC followed by FC in histopathological examination (15,16). Similarly, in our study 90.9% (10/11) of tumors were PTC.…”
Section: Discussionsupporting
confidence: 73%
“…However, studies have observed higher malignancy rate in different clinical settings and recommend reconsideration of malignancy rate and management guidelines in this category (12)(13)(14). In a study which determined the rate of malignancy in 81 thyroid nodules reported as AUS/FLUS, ROM was found 33.3% (15). On the other hand, a study from India ROM of AUS/FLUS cases was 66.7% (16).…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified the PTC follicular variant (39%) and PTC classical (27%) as the commonest forms of thyroid cancer in the study population. Earlier research reported findings that corroborated this result and showed that generally, PTC is the commonest type of thyroid cancer [28]. In fact, 80% of all thyroid malignancies and higher than 90% of the differentiated thyroid cancers are of the PTC variety.…”
Section: Discussionmentioning
confidence: 58%
“… 3–6 The prevalence of malignancy within this category ranges from 5% to 37%. 7 , 8 Some other studies report an even higher malignancy rate, up to 55%, suggesting diagnostic and simultaneous therapeutic lobectomy in cases of AUS/FLUS diagnosis. 9 , 10 The implied risk of malignancy of AUS/FLUS assessed and presented in 2009 in TBSRTC was 5–15%.…”
Section: Introductionmentioning
confidence: 95%